Comparing children's driving abilities in physical and virtual environments. - Gefen, Naomi; Rigbi, Amihai; Archambault, Phillipe S.; Weiss, Patrice L. (Disability & Rehabilitation: Assistive Technology, 2021)
To compare children's driving abilities in a physical and virtual environment and to validate the McGill Immersive Wheelchair Simulator (MiWe-C) for the use of children with disabilities. Participants included 30 children (17 males, 13 females; mean age 14 y 1 mo, [SD 3 y 6 mo]; range: 5–18 y) with cerebral palsy, neuromuscular disease and spinal cord injury. All children were proficient drivers with more than 3 months' experience, who had their own powered wheelchairs. Participants drove a 15-minute physical route and high-fidelity simulation of that route in a counterbalanced order. Performance of the two routes was compared using the 32 item Powered Mobility Programme (PMP). Differences between the driving modes were analyzed with the non-parametric Wilcoxon signed-rank test. Significance was set at α = 0.05. The scores for the total PMP score as rated during both simulator wheelchair driving and during physical driving were very high (M = 4.90, SD = 0.20; M = 4.96, SD = 0.12, respectively) with no significant difference between them (z= −1.69, p =.09). Five out of the 32 PMP tasks showed significant differences between driving modes (narrow corridors, crowded corridors, doorway, sidewalks), with higher scores for the physical driving mode. Having a validated powered mobility simulator for children provides a viable option for an additional practice mode. The MiWe-C simulator is affordable and a user-friendly simulator that can be used anywhere including at home and in school. Children can be independent when practicing even if they are not yet proficient drivers since continual adult assistance is not needed. Having a validated powered mobility simulator for children provides a viable option for an additional practice mode. The MiWe-C is now validated to be used with children 5–18 years with physical disabilities. The MiWe-C is one of the few options for children to practice outside of a research environment.